POLITICAL ACTIVITIES OF THE ROMAN CATHOLIC CHURCH IN INDEPENDENT LATVIA - Malahovskis, Vladislavs (Via Latgalica, 2009)
The aim of the paper is to reflect the political activities of the Roman Catholic Church in two periods of the history of Latvia and the Roman Catholic Church in Latvia – in the period of First Independence of the Republic of Latvia, basically in the 1920s, and in the period following the restoration of Latvia’s independence. With the foundation of the independent state of Latvia, the Roman Catholic Church experienced several changes; - bishops of the Roman Catholic Church were elected from among the people; - the Riga diocese was restored the administrative borders of which were coordinated with the borders of the state of Latvia; - priests of the Roman Catholic Church were acting also in political parties and in the Latvian Parliament. For the Church leadership, active involvement of clergymen in politics was, on the one hand, a risky undertaking (Francis Trasuns’ experience), but, on the other hand, a necessary undertaking, since in this way the Roman Catholic Church attempted to exercise control over politicians and also affect the voters in the elections for the Saeima. The status of the Church in the State of Latvia was legally secured by the concordat signed in the spring of 1922 which provided for a range of privileges to the Roman Catholic Church: - other Christian denominations in Latvia are functioning in accordance with the regulations elaborated by the State Control and confirmed by the Ministry of the Interior, but the Roman Catholic Church is functioning according to the canons set by the Vatican; - releasing the priests from military service, introduction of the Chaplaincy Institution; - releasing the churches, seminary facilities, bishops’ apartments from taxes; - a license for the activity of Roman Catholic orders; - the demand to deliver over one of the church buildings belonging to Riga Evangelical Lutherans to the Roman Catholics. With the regaining of Latvia’s independence, the Roman Catholic Church of Latvia again took a considerable place in the formation of the public opinion and also in politics. However, unlike the parliamentarian period of the independent Latvia, the Roman Catholic Church prohibited the priests to involve directly in politics and considered it unadvisable to use the word “Christian” in the titles of political parties. Nowadays, the participation of the Roman Catholic Church in politics is indirect. The Church is able to influence the public opinion, and actually it does. The Roman Catholic Church does not attempt to grasp power, but to a certain extent it can, at least partly, influence the authorities so that they count with the interests of Catholic believers. Increase of popularity of the Roman Catholic Church in the world facilitated also the increase of the role of the Roma Catholic Church in Latvia. The visit of the Pope in Latvia in 1993 was a great event not only for the Catholic believers but also for the whole state of Latvia. In the autumn of 2002, in Rome, a concordat was signed between the Republic of Latvia and the Vatikan which is to be classified not only as an agreement between the Roman Catholic Church in Latvia and the state of Latvia but also as an international agreement. Since the main foreign policy aim of Latvia is integration in the European Union and strengthening its positions on the international arena, Vatican as a powerful political force was and still is a sound guarantee and support in international relations.